Fostering mathematical connections and habits of mind: A problem-based learning module for elementary education - Purnomo, Yoppy Wahyu; Nabillah, Rokhmatun; Aziz, Tian Abdul; Widodo, Sri Adi (IKIP Siliwangi and I-MES, 2024)
Previous research has highlighted the challenges of improving students' mathematical skills, particularly in connecting mathematical concepts to everyday life and developing strong mathematical habits of mind. This research aims to integrate problem-based learning (PBL) into a mathematics module to enhance mathematical connection abilities and mathematical habits of mind. The ADDIE method was employed to achieve this goal, encompassing five stages: Analysis, Design, Development, Implementation, and Evaluation. The findings indicate that media, material, and language experts deemed the module highly suitable. Furthermore, the product was rated as highly practical based on teacher assessments, student responses, and observations during implementation. Effectiveness tests of the product, conducted through MANOVA, t-tests, and N-gain tests, revealed that the module is highly effective in enhancing students' mathematical connection abilities and moderately effective in improving their mathematical habits of mind. These findings underscore the importance of integrating digital learning technologies to increase the module's engagement and accessibility.